Extracapsular vs standard approach in hip arthroscopy - Di Benedetto, Paolo; Barbattini, Paolo; Povegliano, Lorenzo; Beltrame, Alessandro; Gisonni, Renato; Cainero, Vanni; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2016)
Background: Over the last decades, the arthroscopic treatment of hip pathology has highly grown thanks to the evolution of surgical and diagnostic techniques and instrumentation development. Furthermore the higher life expectancy and functional request make younger patients to be evaluated more frequently for non-arthrosic hip pathologies like labral lesion, FAI, cartilage tears. Treatment substantially has to be chosen between arthroscopy and arthrotomy. This study pretends to compare the clinical outcome between two different arthroscopic access techniques: the traditional one and the extrarticolar one (OUT-IN) we are using regularly in our clinic. Methods: From 2012 to 2014, 37 patients with FAI were treated with traditional technique (Group A) and 28 with extra-articular access (Group B). Indication to surgery treatment was given on the basis of radiological imaging (Pelvis Rx, Hip Rx in AP, Frog Leg view, Dunn view, Pelvic MRI) (8, 9), dynamic range of motion, clinical examination and functional scores (MHHS, MHOT). Pain was scored with NRS. Minimum follow up for each patient was 12 month with clinical controls and functional score recording at 3-6-12 month after surgery. Complications or iatrogenic lesions were assessed. Results: At 12 month after surgery there was no statistically significant differences in hip R.O.M., MHHS and MHOT (33) score. We observed an higher number of iatrogenic lesions and complications in the group A (standard technique) than group B. Conclusions: Hip arthroscopy is a viable and reproducible alternative technique when treating articular lesion such as femur-acetabular impingement and it is demonstrated by the increase of functional score. We can furthermore appreciate that an extra-articular access technique leads to a vary good outcome both in hip R.O.M. and functional scores and has a very low number of complications and iatrogenic lesions.